1994
DOI: 10.1063/1.111987
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent characteristics of a novel porous silicon structure formed in a nonaqueous electrolyte

Abstract: Novel porous silicon layers which photoluminesce and electroluminesce in an aqueous solution have been formed by oxidation of (100) silicon in anhydrous acetonitrile-HF solutions. The novel porous structures consisted of large, noninterconnected pores, 1-2 pm diam, which grew normal to the surface. The pores were spaced 2-3 pm apart, and the length, which could be over 150 pm, was dependent on etch time and current density. Microporous structures (i.e., Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Thus it can be concluded that the formation of silicon oxides plays a major role in producing luminescent Si nanostructures in PSi layers. This hypothesis is supported further by the experimental results of Propst et al [30]. They used nonoxidative, anhydrous HF solutions to obtain PSi layers.…”
Section: Emission Intensitysupporting
confidence: 51%
“…Thus it can be concluded that the formation of silicon oxides plays a major role in producing luminescent Si nanostructures in PSi layers. This hypothesis is supported further by the experimental results of Propst et al [30]. They used nonoxidative, anhydrous HF solutions to obtain PSi layers.…”
Section: Emission Intensitysupporting
confidence: 51%
“…PL spectra corresponding to samples prepared in each solution with the same anodization conditions, current density (56.5 mA cm -2 ), anodization time (10 min) and resistivity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] cm, are shown in Figure 3. PL spectrum for sample produced from HF-MeCN solution presented a blue shift peak that may depend on the pore depth and diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, HF-ethanol has been used by most research groups as the standard electrolyte for PS formation process. After that, Propst et al 6 have reported the electrochemical oxidation of p-and n-type silicon in nonaqueous electrolyte of HF-MeCN and discussed their singular and large porous structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations